Data from: Peacefully extreme - loss of combative strategies in the unstressed, sugar-xerophilic mould, Xeromyces bisporus - Leong, Su-Lin L.; Lantz, Henrik; Vinnere-Pettersson, Olga; Frisvad, Jens C.; Thrane, Ulf; Heipieper, Hermann J.; Dijksterhuis, Jan; Grabherr, Manfred; Pettersson, Mats; Tellgren-Roth, Christian; Schnurer, Johan (Uppsala University, 2014)
Annotation in GFF3-format for the draft genome of Xeromyces bisporus. Genome available for download at EMBL, accession nr. PRJEB6149.
Keywords: Genome annotation data; Medical and Health Sciences; Medicin och hälsovetenskap